Inland open water fisheries of India: Emerging challenges - Bhattacharjya, B. K. (Journal of the Inland Fisheries Society of India, 2022)
India is a riverine country. Its civilizations are heavily dependent on rivers and other inland water bodies, and fisheries has been a part of living since millennia. Indian inland fisheries is believed to have evolved as a livelihood activity of people living along the vast and varied inland waters like rivers, estuaries, lagoons, wetlands, upland lakes, ponds and community tanks, etc. In recent times, considerable water-spread areas have been created in the form of canals and reservoirs. These inland open water bodies constitute important capture fisheries resources of the country. Rivers and associated open water bodies (e.g., reservoirs, estuaries, floodplain wetlands and canals) remained the mainstay of inland capture fisheries of India. These vast and varied inland aquatic ecosystems support rich ichthyofauna (930 fish species belonging to 326 genera). The riverine capture fishery resources comprises five major river systems, viz., the Ganges, the Brahmaputra and the Indus river system in the north and the Peninsular east coast and the West coast river systems in the south. Fourteen large rivers, each with catchment area exceeding 20,000 km2 , form 83% of the drainage area of the country. The next group of 44 rivers constitutes another 7% of the total area and the rest 10% is constituted by many minor rivers. These rivers together constitute a vast network of over 164,000 km in length, beside nearly 65,000 km of canals. The potential of riverine systems as fishing resource varies from stretch to stretch, between the rivers and also within a river. There is paucity of data on fish catch from Indian rivers; studies made by ICAR-Central Inland Fisheries Research Institute in some stretches of River Ganga, Brahmaputra, Godavari, Narmada, Tapti, Krishna and others indicated wide variations in their fish yield, ranging from 5 to 3,300 kg/km.